Oddychanie w rozwoju dziecka i edukacji = Breathing in child development and education - Banasiak-Macherska, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article highlights the impact of breathing through the nasal passage on the development of different areas of human functioning during growth, including the functioning of the child at school. Mouth breathing is undoubtedly known to contribute to a number of abnormalities, leading to various disorders in, among others, transverse craniofacial growth, the eruption of the dentition, its condition and quality, malocclusion, the execution of primary functions and articulatory defects, as well as behavioural, concentration and attention disorders and the microbiota of the upper respiratory tract and its impact on the child`s immunity.
Keywords: respiration; microbiota; hyperactivity; education; development; oddychanie; mikrobiota; nadpobudliwość; edukacja; rozwój